Four eye-witness accounts of Bellingshausen's antarctic voyage of 1819–21 - Armstrong, Terence (Polar Record, 1951)
Recently Soviet writers have claimed that Bellingshausen discovered the Antarctic mainland. The weakness of this argument when it is based upon Bellingshausen's own account of the voyage has been made clear in a previous note in this journal. The revival of interest has, however, brought to light several forgotten or hitherto unpublished eyewitness accounts and it is now possible to decide whether the authors held different views from Bellingshausen as to the discoveries made by the expedition.